Magnesium sulphate and cardiovascular and cerebrovascular adaptations to asphyxia in preterm fetal sheep. (8th July 2015) - Galinsky, Robert; Davidson, Joanne O.; Drury, Paul P.; Wassink, Guido; Lear, Christopher A.; van den Heuij, Lotte G.; Gunn, Alistair J.; Bennet, Laura
Abstract : Key points: Magnesium sulphate is the recommended treatment for pre‐eclampsia and is now widely recommended for perinatal neuroprotection. MgSO4 has vasodilatory and negative inotropic effects; however, it is unknown whether it impairs the cardiovascular and cerebrovascular adaptations to acute asphyxia in preterm fetuses. Intravenous infusion of a clinically comparable dose of MgSO4 to the preterm fetus was associated with no change in blood pressure, reduced fetal heart rate and increased femoral arterial conductance and blood flow; femoral arterial waveform height and width were increased, consistent with increased stroke volume during MgSO4 infusion. During asphyxia MgSO4 was associated with increased carotid and femoral arterial conductance and blood flows; after asphyxia, fetal heart rate was lower and carotid and femoral blood flows and vascular conductance were greater in MgSO4 ‐treated fetuses. These data demonstrate that MgSO4 may increase perfusion of peripheral vascular beds during adverse perinatal events such as asphyxia. Abstract: Magnesium sulphate is a standard therapy for eclampsia in pregnancy and is widely recommended for perinatal neuroprotection during threatened preterm labour. MgSO4 is a vasodilator and negative inotrope. Therefore the aim of this study was to investigate the effect of MgSO4 on the cardiovascular and cerebrovascular responses of the preterm fetus to asphyxia. Fetal sheep were instrumented at 98 ± 1 days of gestation (term = 147 days). At 104 days, unanaesthetised fetuses were randomly assigned to receive an intravenous infusion of MgSO4 ( n  = 6) or saline ( n  = 9). At 105 days all fetuses underwent umbilical cord occlusion for 25 min. Before occlusion, MgSO4 treatment reduced heart rate and increased femoral blood flow (FBF) and vascular conductance compared to controls. During occlusion, carotid and femoral arterial conductance and blood flows were higher in MgSO4 ‐treated fetuses than controls. After occlusion, fetal heart rate was lower and carotid and femoral arterial conductance and blood flows were higher in MgSO4 ‐treated fetuses than controls. Femoral arterial waveform height and width were increased during MgSO4 infusion, consistent with increased stroke volume. MgSO4 did not alter the fetal neurophysiological or nuchal electromyographic responses to asphyxia. These data demonstrate that a clinically comparable dose of MgSO4 increased FBF and stroke volume without impairing mean arterial pressure (MAP) or carotid blood flow (CaBF) during and immediately after profound asphyxia. Thus, MgSO4 may increase perfusion of peripheral vascular beds during adverse perinatal events. Key points: Magnesium sulphate is the recommended treatment for pre‐eclampsia and is now widely recommended for perinatal neuroprotection. MgSO4 has vasodilatory and negative inotropic effects; however, it is unknown whether it impairs the cardiovascular and cerebrovascular adaptations to acute asphyxia in preterm fetuses. Intravenous infusion of a clinically comparable dose of MgSO4 to the preterm fetus was associated with no change in blood pressure, reduced fetal heart rate and increased femoral arterial conductance and blood flow; femoral arterial waveform height and width were increased, consistent with increased stroke volume during MgSO4 infusion. During asphyxia MgSO4 was associated with increased carotid and femoral arterial conductance and blood flows; after asphyxia, fetal heart rate was lower and carotid and femoral blood flows and vascular conductance were greater in MgSO4 ‐treated fetuses. These data demonstrate that MgSO4 may increase perfusion of peripheral vascular beds during adverse perinatal events such as asphyxia.